Penguatan Karakter Peserta Didik Melalui Projek Penguatan Profil Pancasila dan Profil Pelajar Rahmatan Lil’alamin (P5 PPRA) di Kelas V MI Datok Sulaiman Palopo (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to describe the implementation of the Pancasila Student Profile Strengthening Project (P5) and the Rahmatan Lil' Alamin Student Profile (PPRA) in class V of MI Datok Sulaiman Palopo as an effort to strengthen character education. This study uses a qualitative approach with data collection techniques in the form of interviews, observations, and documentation. Data analysis was carried out through the stages of reduction, presentation, and conclusion drawing to obtain a comprehensive picture of the project implementation. The results showed that the character values in PPK were harmoniously integrated with P5 and PPRA, covering cognitive, affective, and psychomotor aspects. The stages of project implementation include planning, theme introduction, activity implementation, exhibition of results, and evaluation. Factors supporting success include the religious culture of the madrasah, parental involvement, and community support through mutual cooperation activities. The obstacles encountered were time constraints and uneven student participation. Overall, the implementation of this project had a positive impact on improving the discipline, responsibility, social awareness, tolerance, creativity, and cooperation of the students, while also strengthening the implementation of the Merdeka Curriculum and Islamic values in madrasahs.